Deliberately dispatched SCR firing angles for harmonic mitigation in three-phase multi-drive systems without communication - Yang, Y.; Davari, P.; Zare, Firuz; Blaabjerg, F. (2016)
© 2016, Institution of Engineering and Technology. All rights reserved. Adjustable Speed Drives (ASDs) are widely used in three-phase multi-drive applications in industry, where low-cost Diode Rectifiers (DRs) or Silicon-Controlled Rectifiers (SCRs) are still employed as the front-ends in practice, also for simplicity. However, the associated harmonics are produced at the grid, which has to be addressed properly according to increasingly stringent standards and/or grid-connection rules. Currently, communication technologies are still not of much cost-effectiveness, and hence, the use of communication in multiple parallel motor-drive systems for harmonic control is rarely witnessed in industry. In this sense, this paper proposes a harmonic mitigation strategy for multiple parallel ASD systems, where the firing angles of the SCR units are deliberately dispatched among the SCR drive units, resulting in certain phase shifts of the SCR currents on purpose. In such a manner, the harmonics appearing in the grid can be mitigated to some extent in multi-drive systems without communication. Simulations are carried out to verify the discussion.